Dynamic regulation of plasmodesmatal permeability and its application to horticultural research. Issue 1 (6th April 2019) - Sun, Yanbiao; Huang, Dingquan; Chen, Xu
Abstract: Effective cell-to-cell communication allows plants to fine-tune their developmental processes in accordance with the prevailing environmental stimuli. Plasmodesmata (PD) are intercellular channels that span the plant cell wall and serve as cytoplasmic bridges to facilitate efficient exchange of signaling molecules between neighboring cells. The identification of PD-associated proteins and the subsequent elucidation of the regulation of PD structure have provided vital insights into the role of PD architecture in enforcing crucial cellular processes, including callose deposition, ER–Golgi-based secretion, cytoskeleton dynamics, membrane lipid raft organization, chloroplast metabolism, and cell wall formation. In this review, we summarize the emerging discoveries from recent studies that elucidated the regulatory mechanisms involved in PD biogenesis and the dynamics of PD opening-closure. Retrospectively, PD-mediated cell-to-cell communication has been implicated in diverse cellular and physiological processes that are fundamental for the development of horticultural plants. The potential application of PD biotechnological engineering represents a powerful approach for improving agronomic traits in horticultural crops in the future. Intercellular channels: managing communications: Modifying the structure and dynamics of plasmodesmata (PD), channels that directly connect the cytoplasm of neighboring plant cells, could improve the growth and productivity of horticultural crops. Xu Chen and colleagues at Fujian Agriculture and Forestry University, China, review recent understanding of the mechanisms regulating the opening and closing of PD and potential applications of this knowledge. Changes in the levels of the sugar polymer callose or phospholipids lining the membrane of PD, or disrupted delivery and transport of PD-associated proteins affect the channels' permeability. Modulating PD dynamics could not only enhance plant survival, by preventing the spread of pathogens and improving their response to changing environmental conditions, but also influence crop yield by aiding the transport of nutrients into fruits and the establishment beneficial symbioses.